2007
DOI: 10.1039/b700375g
|View full text |Cite
|
Sign up to set email alerts
|

Organoditelluride-mediated catalytic S-nitrosothiol decomposition

Abstract: An organoditelluride (5,59-ditelluro-2,29-dithiophenecarboxylic acid) and a polymeric derivative thereof are shown to exhibit catalytic decomposition of S-nitrosothiols such as S-nitrosoglutathione (GSNO) and S-nitrosocysteine (CySNO).Physiological S-nitrosothiols (RSNOs) such as S-nitrosoglutathione (GSNO), S-nitrosocysteine (CySNO), and S-nitrosoalbumin (AlbSNO) are known to serve as storage and transfer agents of physiologically active nitric oxide (NO). 1 Because of the many biological functions of NO, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…The irradiated solutions were then analyzed using HPLC. It was found that disulfide was the major product in argon saturated solutions, in agreement with earlier reports [5][6][7][8][9]. Meanwhile, in aerated solutions, nitrite was also formed along with disulfide.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The irradiated solutions were then analyzed using HPLC. It was found that disulfide was the major product in argon saturated solutions, in agreement with earlier reports [5][6][7][8][9]. Meanwhile, in aerated solutions, nitrite was also formed along with disulfide.…”
Section: Resultssupporting
confidence: 80%
“…S-Nitrosothiols (RSNO) are generally believed as the bio reservoir for nitric oxide (NO) in a biological system [1] and hence their various ways of decomposition are very relevant [2][3][4][5][6][7]. The bond dissociation energy for S-N bond is between 20 and 32 kcal mol −1 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…All NO generation measurements from RSNO species by the new PU-based NOGP were carried out using an NOA via the same methodology described in several previous papers [16][17][18]. Various RSNOs (GSNO, CySNO, and macromolecular BSA-NO) were freshly prepared by methods reported previously [17,19,32].…”
Section: No Measurements Via a Chemiluminescence No Analyzer (Noa)mentioning
confidence: 99%
“…Amine equivalents in the aminated PU (2) were determined by a conventional colorimetric titration method as a reported elsewhere [18,31]. Three different solutions were prepared as follows; i) colorimetric indicator: 0.1 N NaOH solution was slowly dropped into a solution of bromophenol blue (0.1 g) in MeOH (100 mL) until the solution color changed from pale purple to blue; ii) samples: three solutions of aminated PU (2) (73.1, 73.6, and 71.6 mg, respectively) dissolved in DMAC (5 mL), and a blank solution having only the solvent; and iii) titrating agent: 1.0 mM p-toluenesulfonic acid monohydrate dissolved in isopropanol.…”
Section: Determination Of Free Amine Equivalents In the Aminated Pu (2)mentioning
confidence: 99%
See 1 more Smart Citation